2016
DOI: 10.1371/journal.pone.0145329
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation and Factors Associated with Female Genital Mutilation among Reproductive Age Women in Ethiopia: A National Population Based Survey

Abstract: BackgroundFemale genital mutilation (FGM) is a common traditional practice in developing nations including Ethiopia. It poses complex and serious long-term health risks for women and girls and can lead to death. In Ethiopia, the geographic distribution and factors associated with FGM practices are poorly understood. Therefore, we assessed the spatial distribution and factors associated with FGM among reproductive age women in the country.MethodWe used population based national representative surveys. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
64
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 19 publications
23
64
3
Order By: Relevance
“…Although the relationship was not linear in the bivariate analysis, the results of regression analysis adjusted for confounders showed a significant increase in the odds of reporting FGM among respondents in the lower educational categories. Evidence of the beneficial effect of educational qualification on FGM were also reported in other studies in sub-Saharan Africa (Setegn et al 2016;Achia 2014;Kaplan et al 2013). Oddly enough, although educational level is a strong predicator of wealth status, the results revealed an inverse association between wealth status and reporting of FGM.…”
Section: Discussion and Policy Recommendationsupporting
confidence: 79%
See 1 more Smart Citation
“…Although the relationship was not linear in the bivariate analysis, the results of regression analysis adjusted for confounders showed a significant increase in the odds of reporting FGM among respondents in the lower educational categories. Evidence of the beneficial effect of educational qualification on FGM were also reported in other studies in sub-Saharan Africa (Setegn et al 2016;Achia 2014;Kaplan et al 2013). Oddly enough, although educational level is a strong predicator of wealth status, the results revealed an inverse association between wealth status and reporting of FGM.…”
Section: Discussion and Policy Recommendationsupporting
confidence: 79%
“…According to previous reports, the prevalence ranged from 41% to as high as 62.9% at national and subnational levels (Okeke et al 2012;Obi 2004). These estimates are lower than Ethiopia (74%) (Setegn et al 2016) and Gambia (75.6%) (Kaplan et al 2013), but higher than Kenya (28.2%) (Achia 2014) and Tanzania (15%) (Awodele et al 2011). Apart from the high overall prevalence, there has been an increasing trend in FGM in Nigeria since 2003.…”
Section: Discussion and Policy Recommendationmentioning
confidence: 95%
“…On the other hand, the practice is high as compared with similar survey reports of Egypt, 12% [34], Kenya, 3% [35], chad, 10% [33,36] Like other studies [24,39], this study identified maternal age, household wealth index, maternal education, number of living children, perceived religious believes to FGM/C, opinions of women towards the practice of FGM/C, and regular media exposure as individual level factors associated with the practice of FGM/C.…”
Section: Discussionmentioning
confidence: 66%
“…It showed that age at circumcision for girls whose mothers lived in urban was prolonged by the factor of = 1.524 when rural is used as reference. A similar study that has been conducted in Ethiopia by Setegn et al (2016) revealed as the rural girls were more vulnerable towards circumcision than urban girls. The findings of this study also exposed that the educational level of girls mothers had a significant effect on the survival of age at circumcision with 5% level of significance and it prolonged age at circumcision by the factor of = 3.119 and 3.933 for secondary and higher education respectively when illiterate mothers was used as the reference category.…”
Section: Discussionmentioning
confidence: 58%